Developing benders decomposition algorithm for a green supply chain network of mine industry: Case of Iranian mine industry - Mahdi Yousefi Nejad Attari; Ali Ebadi Torkayesh (Operations Research Perspectives, 2018)
This paper attempts to design a three-echelon supply chain network for mine industry considering suppliers, manufacturing centers and distributors with different kinds of vehicles. A multi-objective mixed integer programming model is proposed to minimize transportation costs, shortage costs, purchase costs, production costs and CO2 emissions of vehicles with fuzzy demand values. e-constraint method is used in order to convert multiple objective functions to a single objective function. Benders decomposition algorithm is applied to solve the model under three demand-based scenarios. A case study is done on Iranian mine industry to present the significance and applicability of the proposed model in a real-life case problem as well as the efficiency of Benders decomposition.
Keywords: 330; Supply chain management; Benders decomposition; Iranian mine industry; E-constraint method